STUDENT TEACHERS’ CHALLENGES TOWARD ACTION RESEARCH IN TEACHER EDUCATION COLLEGE - Srieng , Kimsron; Kong, Sam Ol; Srun , Sienghour (Science Education, Institut Agama Islam Negeri Ponorogo, 2025)
Research activities provide an important aspect of graduate students, and it promotes critical thinking, reasoning and rational decision making among the researchers. However, doing research is not easy for students; especially, students who has never conducted research. This study aimed to highlight challenges of student teachers facing with action research implementation. Cross-sectional descriptive research was conducted using a self-administered questionnaire via google form distributed to 184 student teachers from primary and lower secondary in 12+4 program in Phnom Penh Teacher College (PTEC). The questionnaire consisted of two sections with questions aimed at collecting demographic data and data regarding perspective of student teachers towards difficulties of the student-researchers. Data was analyzed by using SPSS version 22. Descriptive and inferential statistics were calculated. The results show that student teachers had many challenges on research knowledge and skills. These challenges derived from student-related challenges, mentor-student challenges, and institution-related challenges. The study suggested that student teachers should have more training on practical research skills, rather than theory, proposed to conduct other topics beside teaching and learning method, more follow up student teacher’s research progress, action research in Khmer language should be promoted through PTEC lecturers, and research written format should be specific and unique, not often be changed.